1973
DOI: 10.1038/bjc.1973.167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Protease Inhibitor on the Adhesion of Ehrlich Ascites Cells to Host Cells in vivo

Abstract: Summary.-Ehrlich ascites tumours (EAT) were grown in mice by injecting 1 x 106 cells intraperitoneally. In mice which received one or more injections of 30 mg soybean trypsin inhibitor (TI) i.p. during tumour growth, the number of recoverable tumour cells was significantly reduced by up to 92%. Also, the mean size of these cells was significantly smaller.When the rate of labelled thymidine incorporation in vitro was compared in TItreated and control cells, no significant differences were detected. However, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1974
1974
1985
1985

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…in mice exactly as described by Whur et al (1973). The cells were collected in isotonic saline after 8-10 days' incubation and the surrounding ascitic fluid was separated by centrifugation for 5 min at 300 g. The cells were washed x 6 by centrifugation in isotonic saline to remove all traces of ascitic fluid before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…in mice exactly as described by Whur et al (1973). The cells were collected in isotonic saline after 8-10 days' incubation and the surrounding ascitic fluid was separated by centrifugation for 5 min at 300 g. The cells were washed x 6 by centrifugation in isotonic saline to remove all traces of ascitic fluid before use.…”
Section: Methodsmentioning
confidence: 99%
“…STUDIES ON EHRLICH ASCITES CELLS grown in mice (Whur et al, 1973) showed that when these cells were reinjected into fresh mice together with soybean trypsin inhibitor (SBTI) the tumour cells became deposited as a confluent monolayer on the hosts' internal abdominal surfaces. The authors suggested that the reason for this organized deposition was that the SBTI prevented proteolytic activity of an enzyme on the cell surface.…”
mentioning
confidence: 99%
“…2 Effect8 of aprotinin on tumour growth G-rowth of the tumour, measured by the number of recoverable ascites cells within both saline and aprotinin-treated animals at various times after injection of 106 viable tumour cells is shown in Fig. 4 (Back and Leblanc, 1977;Kinjo et al, 1963;Verloes et al, 1978;Whur et al, 1973) (Hynes, 1976;Talmadge et al, 1974). In vtio however, such effects are t-likely to be less pronounced, due to more rapid catabolism of aprotinin and its widespread binding to ubiquitous sialyl moieties; factors which probably account for its relative inefficiency as a therapeutic agent in the tumour-bearing host, and which are likely to be exaggerated by rapid cell replication and copious ascitic fluid production.…”
Section: Resultsmentioning
confidence: 99%
“…Also, in view of reports that a natural protease inhibitor (soybean trypsin inhibitor) impairs growth of ascites tumours (Whur et al, 1973;Verloes et al, 1978) (Watson, 1958) and lead citrate (Reynolds, 1963) prior to examination in an AEI EM6B transmission electron microscope.…”
mentioning
confidence: 99%
“…in mice, as described by Whur et al (1973). The cells were collected in isotonic saline after 8-10 days' incubation and the surrounding ascitic fluid was separated by centrifugation for 5 min at 300 g. The cells were washed x 6 by centrifugation in isotonic saline before use.…”
Section: Methodsmentioning
confidence: 99%